Fish Intake, Circulating Mercury and Mortality in Renal Transplant Recipients - Sotomayor, Camilo G. (Nutrients, 2018)
Marine-derived omega-3 polyunsaturated fatty acids (n-3 PUFAs) are inversely associated with cardiovascular and all-cause mortality in renal transplant recipients (RTRs). Recommendations to increase marine-derived n-3 PUFAs by increasing fish intake may have a drawback in concomitant stimulation of mercury intake, which could lead to higher circulating mercury concentrations and mitigation of otherwise beneficial effects of n-3 PUFAs. We aimed to monitor circulating mercury concentrations, and to prospectively evaluate whether it counteracts the potential association between fish intake and cardiovascular and all-cause mortality in a cohort of RTRs (n = 604, 53 ± 13 years-old, 57% men) with long-term follow-up (median of 5.4 years; 121 deaths). Circulating mercury concentration (median 0.30 (IQR 0.14–0.63) µg/L) positively associated with fish intake (std. β = 0.21, p < 0.001). Multivariable-adjusted Cox-proportional hazards regression analyses showed that prior to, and after additional adjustment for circulating mercury concentrations, fish intake was inversely associated with both cardiovascular (HR 0.75, 95% CI 0.58–0.96; and, HR 0.75, 95% CI 0.58–0.97, respectively) and all-cause mortality (HR 0.84, 95% CI 0.72–0.97; and, HR 0.86, 95% CI 0.74–0.99, respectively). Secondary analyses accounting for marine-derived n-3 PUFAs intake revealed associations of similar magnitude. In conclusion, we found no evidence of a counteracting effect conferred by circulating mercury concentrations on the associations between fish and marine-derived n-3 PUFAs intake and the risks of cardiovascular and all-cause mortality in RTRs.